Becoming them or remaining us? The impact of communication on immigrant integration. Issue 6 (30th March 2022) - You, Jing; Ma, Yupei
ABSTRACT: We exploit an exogenous introduction of a mobile phone plan among rural-to-urban migrants in Beijing, China, to study the causal impact of communication on immigrant integration and assimilation. More contact via phone calls and social media over a year improves immigrants' language alignment, enhances their perceived similarity with the natives, while attenuates self-identity of and adherence to original cultures. Migrants show stronger settlement intentions in capital cities of native provinces rather than in Beijing, because of more concerns about distant family members and perceived perpetuating discrimination under intervention. Long-term integration, indicated by a sense of belonging, attitudes on inter-group marriage and the importance of their children to learn original languages remains stable.